Drosophila as a Model to Study the Mechanism of Nociception - He, Jianzheng; Li, Botong; Han, Shuzhen; Zhang, Yuan; Liu, Kai; Yi, Simeng; Liu, Yongqi; Xiu, Minghui (Frontiers in Physiology, 2022)
Nociception refers to the process of encoding and processing noxious stimuli, which allow animals to detect and avoid potentially harmful stimuli. Several types of stimuli can trigger nociceptive sensory transduction, including thermal, noxious chemicals, and harsh mechanical stimulation that depend on the corresponding nociceptors. In view of the high evolutionary conservation of the mechanisms that govern nociception from Drosophila melanogaster to mammals, investigation in the fruit fly Drosophila help us understand how the sensory nervous system works and what happen in nociception. Here, we present an overview of currently identified conserved genetics of nociception, the nociceptive sensory neurons responsible for detecting noxious stimuli, and various assays for evaluating different nociception. Finally, we cover development of anti-pain drug using fly model. These comparisons illustrate the value of using Drosophila as model for uncovering nociception mechanisms, which are essential for identifying new treatment goals and developing novel analgesics that are applicable to human health.